E-018 Embolisation of Intracranial Arteriovenous Malformations and Dural Arteriovenous Fistulae Using a Novel Low Profile Distal Access Microcatheter: Initial experience. (14th July 2013) - Tekle, W; Jagadeesan, B; Siddiq, F; Khan, A; Grande, A; Tummala, R
Abstract : Introduction: Successful endovascular embolisation of intracranial arteriovenous malformations (AVMs) or arteriovenous fistulae (AVFs) requires distal navigation of very small microcatheters to the nidus or fistulous point of the malformation. Such small microcatheters can only be navigated by flow direction or over 0.008 or 0.010 microwires, and the lack of support from these microwires often makes distal navigation challenging. Further, these small microcatheters are sometimes prone to rupture from the high injection pressures used during embolisation or retention within the feeding artery after embolisation. Additionally, not all of them are compatible with Ethylene Vinyl Alcohol Co-polymer (Onyx), which is currently the most widely used liquid embolic agent. Herein we report our initial experience with successful distal navigation of a small but robust microcatheter over a 0.014 wire system and subsequent successful embolisation using either Onyx or n-Butyl Cyano-acrylate (n-BCA). Materials and Methods: A series of 6 patients (4 men, age 38–80 years) presented to our hospital with intracranial AVMs and dural AVFs. Of these 3 were ruptured Borden Type III dural AVFs and 3 were pial AVMs (2 ruptured, 1 with hemiplegia, proptosis). In each of these malformations, we navigated a "Headway Duo" microcatheter [156 cm long, 0.34 ml dead space, 2.6 French (proximally) and 1.6 French (distally), Microvention, Tustin, Ca, USA], which is Onyx and n-BCA compatible, in combination with a Synchro 2 microwire (Stryker, Fremont, Ca, USA) to the nidus/fistulous point of these malformations. We performed embolisation using a mixture of Onyx 18 and Onyx 34 with or without coils or using nBCA in each instance. Results: We achieved successful navigation of the headway DUO microcatheter over a 0.014 microwire system and accessed the nidus/fistulous point in each of these malformations. Subsequently, we were able to successfully embolise the malformation using Onyx in 10 vessels, n-BCA in 2 vessels, in a total of 6 malformations in 6 patients. In one patient, we were also able to place coils in 3 feeder branches by using this microcatheter system in order to reduce the flow rate as a prelude to liquid embolisation. There was no instance of vascular injury, catheter rupture, or catheter retention. No patient had clinical deficits related to embolisations. Two of the three AVMs underwent surgery after pre-surgical embolisations, one is awaiting surgery. Angiographic cure was achieved with endovascular embolisation in 2 out of the 3 AVFs, and by surgical disconnection of the fistula in one. Conclusion: We were able to safely and successfully perform endovascular embolisation of a series of intra-cranial arterial malformations using a new robust but small diameter microcatheter in combination with Onyx or n-BCA after successful navigation of this microcatheter to the nidal or fistulous point over a 0.014 wire system. Disclosures: W. Tekle: None. B. Jagadeesan: None. F. Siddiq: None. A. Khan: None. A. Grande: None. R. Tummala: None.